BOOK REVIEW OF NICHOLAS SPARKS’ SAFE HAVEN - Putriyani, Maygananda (LANTERN (Journal on English Language, Culture and Literature), 2015)
Safe Haven (2010) is a novel written by Nicholas Sparks. It is a story about a woman who suffers from traumatic experience due to her abusive husband. She manages to escape to a safe place and find happiness in that place. The woman wants to start a new life even though the shadow of the past will always haunt her.